2016
DOI: 10.1002/jcp.25575
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial STAT3 Activation Increases Vascular Leakage Through Downregulating Tight Junction Proteins: Implications for Diabetic Retinopathy

Abstract: Vascular inflammation is characteristic feature of diabetic retinopathy. In diabetic retina, a variety of the pro-inflammatory cytokines are elevated and involved in endothelial dysfunction. STAT3 transcription factor has been implicated in mediating cytokine signaling during vascular inflammation. However, whether and how STAT3 is involved in the direct regulation of the endothelial permeability is currently undefined. Our studies revealed that IL-6-induced STAT3 activation increases retinal endothelial perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 45 publications
5
82
0
Order By: Relevance
“…Our results also showed that miR-15a/16 reduced endothelial cell permeability through downregulation of VEGF in REC under high glucose conditions. Inductive roles of VEGF on endothelial permeability have been reported in previous studies (Fischer et al, 1999; Qin et al, 2016; Yun et al, 2016). …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results also showed that miR-15a/16 reduced endothelial cell permeability through downregulation of VEGF in REC under high glucose conditions. Inductive roles of VEGF on endothelial permeability have been reported in previous studies (Fischer et al, 1999; Qin et al, 2016; Yun et al, 2016). …”
Section: Discussionsupporting
confidence: 74%
“…Additionally, it has been shown that VEGF increases endothelial permeability in retinal endothelial cells (Behzadian et al, 2003; Qin et al, 2016; Yun et al, 2016). Our recent study has shown an inhibitory role of miR-15a/16 on the inflammatory signaling of IL-1β, TNFα, NF-κB, as well as retinal leukostasis in vivo (Ye et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses from human patients also reveal a positive association between the presence of pneumonitis and the occurrence of scrub typhus meningitis and meningoencephalitis [47]. At present, it remains unclear how these lung responses influence neuroinflammation, but it has been shown that cytokine-mediated STAT3 activation can down-regulate occludin levels and increase endothelial permeability through the induction of VEGF production in EC [48]. Therefore, it will be important to further examine the molecular mechanisms underlying lung-brain infection and tissue damage and how such changes impact the release of proinflammatory cytokines and endogenous danger signals.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 factors influence endothelial function in DR [34,35]. Thus, we focused on the relationship between O-GlcNAcylation and STAT3 phosphorylation, and changes to specific STAT3 sites under different O-GlcNAcylation levels.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 activation is also one of the main facilitators of BRB breakdown through increased VEGF expression [24] and downregulation of endothelial tight junction protein expression [25]. STAT3 proteins are targets of phosphorylation [24] focused on the sites of Tyr705 and Ser727 [26].…”
Section: Introductionmentioning
confidence: 99%